Ответы и объяснения

2013-07-21T08:27:28+00:00
(2x+3)^(1/2)-(2x-3)^(1/2)=1
возводим в квадрат
2x+3+2x-3+2sqrt((2x+3)(2x-3))=1
2sqrt((4x^2-9)=1-4x
возводим в квадрат снова
4(4x^2-9)=1+16x^2-8x
16x^2-36-1-16x^2+8x=0
x=37/8
  • AlbuRin
  • светило науки
2013-07-21T08:56:01+00:00
(2x  +  3)^(1/2)  -  (2x  -3)^(1/2)  =  1
ОДЗ   2x  +  3  >=0,    x  >=  -1.5                ОДЗ  x  >=  1.5
          2x  -  3   >=  0   x  >=  1,5
Возведём  обе  части  уравнения  в  квадрат.
2x  +  3  +  2x  -  3  -  2(4x^2  -  9)^(1/2)  =  1
2(4x^2  -  9)^(1/2)  =  4x  -  1
Ещё  раз  возведём  в  квадрат
16x^2  -  36  =  16x^2  -  8x  +  1 
8x  =  37
x  =  37/8   удовлетворяет   ОДЗ.           
Ответ.      4 5/37